Effect of implementation of the MOREOB program on adverse maternal and neonatal birth outcomes in Ontario, Canada: a retrospective cohort study - Deborah Weiss; Deshayne B. Fell; Ann E. Sprague; Mark C. Walker; Sandra Dunn; Jessica Reszel; Wendy E. Peterson; Doug Coyle; Monica Taljaard (BMC, 2019)
Abstract Background In 2002, the MOREOB (Managing Obstetrical Risk Efficiently) obstetrical patient safety program was phased-in across hospitals in Ontario, Canada. The purpose of our study was to evaluate the effect of the MOREOB program on rates of adverse maternal and neonatal outcomes. Methods A retrospective cohort study, using province-wide administrative hospitalization data. We included maternal and neonatal records between fiscal years 2002-2003 and 2013-2014, for deliveries taking place at the 67 Ontario hospitals where the MOREOB program was implemented between 2002 and 2012. After accounting for institutional mergers and excluding very small hospitals, 55 hospitals (1,447,073 deliveries) were included. Multivariable logistic and linear mixed effects regression analysis were used, accounting for secular trends, within hospital correlation and over time correlation, and adjusting for a maternal comorbidity index, hospital annual birth volume, and level of care. The main outcome measure was a composite individual-level indicator of incidence of any adverse events, and a hospital-level score, called the Weighted Adverse Outcome Score (WAOS) capturing both maternal and neonatal adverse outcomes. Results Across the 12 years of follow up, there were 98,789 adverse maternal and neonatal outcomes, a rate of 6.83 per 100 deliveries (6.66 per 100 occurring before, 6.91 per 100 during, and 6.84 per 100 after program implementation). The multivariable analysis found no statistically significant decrease in adverse events associated with program implementation (OR for adverse events after versus before =1.11 (95% CI: 1.06 to 1.17, change in mean WAOS score after minus before =0.15 (− 0.36 to 0.67)). Conclusions We did not find a reduction in the incidence of maternal and neonatal adverse outcomes associated with the MOREOB program, and small yet statistically significant increases in some adverse events were observed.